Youth custody is no place for mentally ill children and young people. (June 2023) - Haysom, Leigh; Kasinathan, John; Singh, Yolisha
Objective: We review issues with incarcerating mentally ill children and young people in Australia, highlighting key demographics, rates of mental disorders, consideration of brain development, developmental trauma and children's experiences of custody. Methods: Population relevant literature will be outlined as applicable. Results: Children and adolescents in custody have high rates of mental illness, cognitive impairment and comorbid diagnoses. Childhood adversity and trauma impacts on psychosocial development from an early age. Almost half of all young people in custody are First Nations children, a 20 times over-representation. Youth custody is frequently experienced as an additional trauma for young people. Mental health diversion into community treatment is effective and reduces costs to young people, their families, communities and society generally. Conclusion: Youth custody is an inappropriate setting for children and young people with mental disorders, and can be further traumatising. Economic and health benefits for mental health diversion away from youth custody are manifest.